The Effect of Dual Task on Attentional Performance in Children With ADHD - Caldani, Simona; Razuk, Milena; Septier, Mathilde; Barela, José Angelo; Delorme, Richard; Acquaviva, Eric; Bucci, Maria Pia (Frontiers in Integrative Neuroscience, 2019)
Attention-deficit/hyperactivity disorder (ADHD) is a common psychiatric disorder without validated objective markers. Oculomotor behavior and executive motor control could poten-tially be used to investigate attention disorders. The aim of this study was to explore an oculomotor and postural dual task in children with ADHD. Forty-two children were included in the study, gathering children with ADHD (n=21) (mean 8.15 age ± years 0.36) and sex-, age- and IQ-matched typically developing children (TD). Children performed two distinct fixation tasks in three different postural conditions. Eye movements and postural body sway were recorded simultaneously, using an eye tracker and a force platform. Results showed that children with ADHD had poor fixation capability and poor postural sta-bility when compared to TD children. Both groups showed more difficulties to stand up on the unstable platform and displayed more saccades during the fixation task. Surprisingly, in the unstable platform condition and fixation with distractor task, the instability of children with ADHD was similar to that observed in TD children. “Top-down” dys-regulation mediated by frontal-striatal dysfunction could be at the origin of both poor inhibitory oculomotor deficits and impaired body stability reported in children with ADHD. Finally, we could assume that the fact both groups of children focused their attention on a secondary task led to poor postural control. In the future it could be interesting to explore further this issue by developing new dual tasks in a more ecological situation in order to gain more insight on attentional processes in children with ADHD.